Perception of public social responsibility and the quality of municipal management in the province of Tarma - Alcantara-Chagua, Yordy J. (2022)
Objective. To establish the relationship between public social responsibility and the quality of municipal management in the province of Tarma, Huancayo (Peru). Methods. The research had a quantitative approach, basic type, correlational level and non-experimental-cross-sectional design. The sample consisted of 127 citizens of the province of Tarma. The sampling technique was non-probabilistic and intentional. Two instruments were used: the public social responsibility questionnaire and the municipal management quality questionnaire. The first questionnaire consisted of 20 items referring to the dimensions of public social responsibility and the second questionnaire consisted of 16 items referring to the dimensions of municipal management quality. Results. 71.7% of respondents perceived that the management of public social responsibility was of medium level and the quality of municipal management was of moderate level. The hypothesis test concludes that there is a statistically significant relationship between public social responsibility management and municipal management quality, showing a Kendall's Tau-b correlation strength of 0.272. Conclusion. It can be affirmed that the higher the level of positive perception of public social responsibility management, the better the quality of municipal management.